Estudio de factibilidad para el desarrollo de un sistema web para el Almacen Baratodo - Sarzosa Sanchez, Jose Rafael (2021)
The evolution of technology has guided commerce along new paths and horizons, making its way into the internet, revolutionizing the way of buying and selling, through this area the need arises to implement a "Baratodo" commercial web system. By implementing this web system with a virtual store, it will be possible to have an online catalog of products, in addition to obtaining many visits since it will have a live chat for online advice, this technological innovation will allow to increase the number of visits to the store online and therefore maximize the possibilities of purchasing home appliance equipment or technical maintenance services. Providing in this way a better service to its customers and increasing its market segment, not only at the cantonal but also at the provincial level. As a research instrument, the explanatory and quantitative ones were used, which help us to understand in a simpler way the requirements that are lacking in the company. And as a research technique, surveys and interviews were used to determine if the implementation of a web system is feasible.